2005
DOI: 10.1016/j.cub.2005.07.028
|View full text |Cite
|
Sign up to set email alerts
|

BUR Kinase Selectively Regulates H3 K4 Trimethylation and H2B Ubiquitylation through Recruitment of the PAF Elongation Complex

Abstract: Histone-lysine methylation is linked to transcriptional regulation and the control of epigenetic inheritance. Lysine residues can be mono-, di-, or trimethylated, and it has been suggested that each methylation state of a given lysine may impart a unique biological function. In yeast, histone H3 lysine 4 (K4) is mono-, di-, and trimethylated by the Set1 histone methyltransferase. Previous studies show that Set1 associates with RNA polymerase II and demarcates transcriptionally active genes with K4 trimethylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
165
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(182 citation statements)
references
References 37 publications
15
165
1
1
Order By: Relevance
“…2B). Thus, H2B-Lys-123 ubiquitination is dispensable for up-regulation of H3-Lys-4 dimethylation, but not trimethylation, at the coding sequences of the PHO84, ADH1, and PYK1 genes, consistent with a recent study demonstrating the role of H2B-Lys-123 ubiquitination in the regulation of H3-Lys-4 tri-but not dimethylation (48). Similarly, Henry et al (30) have also demonstrated that H3-Lys-4 trimethylation, but not dimethylation, at GAL1 is regulated by H2B-Lys-123 ubiquitination.…”
Section: H2b-lys-123 Ubiquitination Upregulates H3-lys-4 Tri-but Not supporting
confidence: 90%
See 1 more Smart Citation
“…2B). Thus, H2B-Lys-123 ubiquitination is dispensable for up-regulation of H3-Lys-4 dimethylation, but not trimethylation, at the coding sequences of the PHO84, ADH1, and PYK1 genes, consistent with a recent study demonstrating the role of H2B-Lys-123 ubiquitination in the regulation of H3-Lys-4 tri-but not dimethylation (48). Similarly, Henry et al (30) have also demonstrated that H3-Lys-4 trimethylation, but not dimethylation, at GAL1 is regulated by H2B-Lys-123 ubiquitination.…”
Section: H2b-lys-123 Ubiquitination Upregulates H3-lys-4 Tri-but Not supporting
confidence: 90%
“…Similarly, Henry et al (30) have also demonstrated that H2B-Lys-123 ubiquitination regulates only tri-but not dimethylation of H3-Lys-4 at GAL1. Furthermore, a recent biochemical study (48) has demonstrated the role of H2B-Lys-123 ubiquitination in the regulation of only H3-Lys-4 trimethylation. Taken together, H2B-Lys-123 ubiquitination is differentially required for regulation of H3-Lys-4 di-and trimethylation at the active genes, revealing a complex regulation of H3-Lys-4 methylation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We now know that monoubiquitination of H2B is required for H3K4 di-and trimethylation in yeast and that this crosstalk pathway is highly conserved from yeast to human [6,40,41]. Although the past several years brought about a watershed of information regarding the factors/proteins required for proper H2B monoubiquitination [6,[40][41][42][43][44][45][46][47][48], the molecular mechanism for this histone crosstalk was poorly understood. Recent studies in yeast S. cerevisiae demonstrated that monoubiquitination of histone H2B regulates COMPASS' compositional assembly, and therefore, proper H3K4 methylation [49].…”
mentioning
confidence: 99%
“…The first breakthrough came with the identification of the budding yeast protein Bre1 [38,39], which, together with the ubiquitin-conjugating enzyme Rad6, serves as the E3 ligase in the monoubiquitylation of the yeast histone H2B on lysine 123 (K123) within transcribed chromatin [38][39][40][41]. Notably, H2B monoubiquitylation was subsequently found to be required for di-and trimethylation of lysine 4 and lysine 79 of histone H3 at transcribed chromatin [42][43][44][45][46][47][48]. This pathway is conserved from yeast to mammals, and is dependent on a host of additional proteins that converge at the elongating RNA Pol II [41,[49][50][51][52][53][54].…”
mentioning
confidence: 99%